The repetitive portion of the Xenopus IgH Mu switch region mediates orientation-dependent class switch recombination. Issue 2 (October 2015) - Zhang, Zheng Z.; Pannunzio, Nicholas R.; Lu, Zhengfei; Hsu, Ellen; Yu, Kefei; Lieber, Michael R.
Highlights: Xenopus Sμ (XSμ) has a highly repetitive 2 kb region rich in WGCW. The 2 kb XSμ forms R-loops when in the physiologic orientation in B cells. The 2 kb XSμ portion supports Ig CSR in B cells, but only in the forward orientation. The relation between R-loop formation and Ig CSR may be conserved in evolution. Abstract: Vertebrates developed immunoglobulin heavy chain (IgH) class switch recombination (CSR) to express different IgH constant regions. Most double-strand breaks for Ig CSR occur within the repetitive portion of the switch regions located upstream of each set of constant domain exons for the Igγ, Igα or Igϵ heavy chain. Unlike mammalian switch regions, Xenopus switch regions do not have a high G-density on the non-template DNA strand. In previous studies, when Xenopus Sμ DNA was moved to the genome of mice, it is able to support substantial CSR when it is used to replace the murine Sγ1 region. Here, we tested both the 2 kb repetitive portion and the 4.6 kb full-length portions of the Xenopus Sμ in both their natural (forward) orientation relative to the constant domain exons, as well as the opposite (reverse) orientation. Consistent with previous work, we find that the 4.6 kb full-length Sμ mediates similar levels of CSR in both the forward and reverse orientations. Whereas, the forward orientation of the 2 kb portion can restore the majority of the CSR level of the 4.6 kb full-length Sμ, the reverse orientation poorly supports R-looping and no CSR. The forward orientation of the 2 kb repetitive portion has more GG dinucleotides on the non-template strand than the reverse orientation. The correlation of R-loop formation with CSR efficiency, as demonstrated in the 2 kb repetitive fragment of the Xenopus switch region, confirms a role played by R-looping in CSR that appears to be conserved through evolution.